2021
DOI: 10.3389/fimmu.2021.625928
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Immune Response of Yellow Catfish (Pelteobagrus fulvidraco) Infected With Edwardsiella ictaluri Presenting the Inflammation Process

Abstract: Edwardsiella ictaluri is a highly destructive pathogen in cultured yellow catfish, thus it was very necessary to study the immune response of yellow catfish against bacterial infection. In this study, RNA-Seq technology was used to study the immune response in two distinct tissues of yellow catfish at eight different time points (h) after E. ictaluri infection. The number of differentially expressed genes (DEGs) in the spleen and liver was low at 3 h and 6 h post-infection, respectively. Afterwards, the most n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 80 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…The complement has been viewed as a part of the innate immune system which can help to fight microbial intruders, and can quickly tag and remove them directly (Ricklin et al, 2010). Previous studies have showed that the C3 and C4 in the liver were induced significantly at transcription level after E. ictaluri invasion (Zhou et al, 2021). In this study, the expression levels of C3 and C4 genes in the head kidney and liver were upregulated distinctly and then downregulated post S. iniae infection.…”
Section: Discussionmentioning
confidence: 55%
“…The complement has been viewed as a part of the innate immune system which can help to fight microbial intruders, and can quickly tag and remove them directly (Ricklin et al, 2010). Previous studies have showed that the C3 and C4 in the liver were induced significantly at transcription level after E. ictaluri invasion (Zhou et al, 2021). In this study, the expression levels of C3 and C4 genes in the head kidney and liver were upregulated distinctly and then downregulated post S. iniae infection.…”
Section: Discussionmentioning
confidence: 55%
“…For example, Wang et al (2021) found that multifocal necrosis and non‐suppurative inflammation occurred in the hepatopancreas of fish after infection with spring viraemia of carp virus caused by water quality problems, resulting in reduced food intake, weakened stress capacity and eventually death (Liu et al, 2020). Zhou et al (2021) reported that after Edwardsiella invaded fish, it reached the brain along the olfactory nervous system, leading to granulomatous chronic inflammation in the brain. Encephalitis led to abnormal behaviour of diseased fish, such as spastic spiral swimming.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-sequencing technology can effectively reveal genes that are engaged in immune responses and expressed in response to the presence of toxicants or infection (25)(26)(27). Many studies have focused on the transcriptomic changes in different fish tissues after bacterial infection (15,28). However, few studies have reported the combined analysis of RNA-sequencing in the spleen and gill of T. rubripes after V. harveyi infection.…”
Section: Introductionmentioning
confidence: 99%